Derivational Morphemes in Jack Ma’s Speech: Morphology Study - Sri Nirwana Hermapratiwi; Ervina CM Simatupang (Budapest International Research and Critics University, 2022)
This research aims to identify the types of derivational morphemes by inserting affixes that appears in Jack Ma’s speech and to know the derived words that changes the word categories. The method employed was qualitative descriptive to conduct this research. The data taken were fifty that containing derivational morphemes in Jack Ma’s speech. The results indicated that there are two types of derivational morphemes by inserting affix, namely suffix (74%) and prefix (24%). In addition, there are derived words that change to the new word categories, namely noun forming (44%), adverb forming (20%), adjective forming (20%), and verb forming (16%). The word category changed that occur the most in prefix and suffix is noun forming, such as in-, mis-, -dom, -ion, -ity, -ation, -ness, -ee, -ure, -or, -er, and –ment. Additionally, the least word category changed that occur in prefix and suffix is verb forming such as –en, and –ize.